Advancing biomass fermentation and composting for global sustainability: A bibliometric perspective (2019–2024) - Fan Jiao; Xueru Zhu; Chao Li; Haojun Xie; Hua Li (Discover Sustainability)
Abstract With the continuous growth of global food demand and the increasing volume of agricultural waste, timely and effective disposal of waste is crucial for environmental protection and sustainable development. Fermentation and composting are the most effective methods for producing organic fertilizers and treating biomass. To comprehensively understand global research trends, this article uses the Web of Science (WOS) and China National Knowledge Infrastructure (CNKI) databases covering the period from 2019 to 2024 for bibliometric analysis and employs CiteSpace programs for data mapping. A total of 4955 research articles were analyzed, revealing a significant increase in publications on biomass fermentation for organic fertilizer production, particularly due to policy promotion in China and the European Union, which boosted research activities. The analysis revealed that current research hotspots include lignocellulose degradation, microbial community optimization, and environmental pollution control. Additionally, the integration of advanced technologies, such as artificial intelligence and machine learning, has encouraged scholars to explore intelligent fermentation, offering potential benefits in optimizing product processes and enhancing the prediction and control of product yield and performance.